2020
DOI: 10.1038/s41598-020-77987-y
|View full text |Cite
|
Sign up to set email alerts
|

PorA, a conserved C-terminal domain-containing protein, impacts the PorXY-SigP signaling of the type IX secretion system

Abstract: Porphyromonas gingivalis, a periodontal pathogen, translocates many virulence factors including the cysteine proteases referred to as gingipains to the cell surface via the type IX secretion system (T9SS). Expression of the T9SS component proteins is regulated by the tandem signaling of the PorXY two-component system and the ECF sigma factor SigP. However, the details of this regulatory pathway are still unknown. We found that one of the T9SS conserved C-terminal domain-containing proteins, PGN_0123, which we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 65 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…The genes required for these processes fall into 2 broad groups (Table ). The first group of genes codes for components of the T9SS machinery, including IM proteins (PorL and PorM), OM associated proteins (PorE, PorF, PorG, PorK, PorN, PorP, PorQ, PorT, PorU, PorV, PorW, PorZ, and Sov) (Sato et al 2010;Naito et al 2019), and components involved in signal transduction and gene regulation (PorA, PorX, PorY, and SigP) (Yukitake et al 2020). Besides PorA, all of these proteins have orthologs in T. forsythia and P. intermedia (Table ).…”
Section: The T9ss Loads the Outer Membrane With Virulence Factors For...mentioning
confidence: 99%
“…The genes required for these processes fall into 2 broad groups (Table ). The first group of genes codes for components of the T9SS machinery, including IM proteins (PorL and PorM), OM associated proteins (PorE, PorF, PorG, PorK, PorN, PorP, PorQ, PorT, PorU, PorV, PorW, PorZ, and Sov) (Sato et al 2010;Naito et al 2019), and components involved in signal transduction and gene regulation (PorA, PorX, PorY, and SigP) (Yukitake et al 2020). Besides PorA, all of these proteins have orthologs in T. forsythia and P. intermedia (Table ).…”
Section: The T9ss Loads the Outer Membrane With Virulence Factors For...mentioning
confidence: 99%
“…2A ), indicating that their presence in the pulldown assay was specific to the presence of Sov. PorA was recently demonstrated to be a component of the T9SS and is also known as a substrate of the T9SS ( 26 ). The specific enrichment of many T9SS components in the Sov coimmunoprecipitated material suggests a large T9SS interactome involving Sov.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, PPI was not identified to interact with Sov; however, surprisingly, we found PorA to be part of the PorV-Sov complex in P. gingivalis . PorA was recently shown to be an essential component of the T9SS and shown to be involved in signal transduction as part of the PorXY-SigP regulatory system ( 26 ). PorA is also a cargo protein that, like other cargo, is secreted, binds to PorV, has its CTD signal removed, and is conjugated to A-LPS ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PorX (PG0928), which is the cytoplasmic response regulator of T9SS expression detected in both proteomes, was not detected in the pull-down eluates. However, PorA (PG2172), the putative outer membrane relay protein of the PorXY-SigP signaling pathway ( Yukitake et al., 2020 , Gorasia et al, 2022 ) was detected in the pull-down eluate. PorX was enriched in the A7UF proteome, but PorA was enriched in the W83 proteome.…”
Section: Resultsmentioning
confidence: 99%